Dimerization of Aromatic Compounds Using Palladium-Carbon-Catalyzed Suzuki–Miyaura Cross-Coupling by One-Pot Synthesis - Du, Fangyu; Zhou, Qifan; Liu, Dongdong; Fang, Ting; Shi, Yajie; Du, Yang; Chen, Guoliang (Synlett, 2018)
The aromatic dimers play a significant role in many aspects. Herein, we report a simple palladium-carbon catalyst that is highly effective for the dimerization of brominated aromatic compounds under mild conditions using abundant brominated aromatic compounds, bis(pinacolate)diboron and potassium acetate by a ‘one-pot’ method. This process, which we believe proceeds via a Suzuki–Miyaura cross-coupling reaction mechanism, allows access to a variety of aromatic compounds under mild reaction conditions and has a good functional group tolerance with moderate to high yields.
Keywords: self-coupling; Suzuki–Miyaura cross-coupling; palladium-carbon; catalysis; dimerization